Integrating TQM and TPM into a management information system. (19th April 2004) - Sharp, J.M.; Irani, Z.; Kutucuoglu, K.; Erzincanli, F.
Many manufacturing SMEs (small to medium enterprises) encounter problems when maintaining production equipment. This is often because insufficient time is spent, particularly by SMEs, on developing the role of maintenance to improve manufacturing performance. This paper discusses the role of total productive maintenance (TPM) in creating a total quality management (TQM) environment in the maintenance function of manufacturing SMEs. TQM and TPM have significant similarities such that it can be ascertained that quality and success depend on the efforts of everyone within the organisation. Therefore these two management philosophies of TQM and TPM can be analysed and compared. In looking at the similarities that show these philosophies are complementary, the paper reveals the possible reinforcement effects when they are integrated together in an SME. It discusses the initial findings of case study research with three SME companies who are striving to improve the quality of maintenance within their organisations.